PERAN NILAI KERJA EMPAT FAKTOR DAN KEPEMIMPINAN DENGAN KONTRAK PSIKOLOGIS SEBAGAI MEDIATOR TERHADAP TIM KERJA EFEKTIF - Fitlya, Rizki (Universitas Ahmad Dahlan, 2016)
AbstractThis reserach aims to explore the role of work value factors, transactional dan transformational leadership type, psychological contract to team effectiveness and examined the variables that give significant contribution to team effectiveness. This research involved 170 of medical and non-medical employee in X Hospital, Pontianak. Effective team work scale, psychological contract scale, transformational and transactional leadership scale and work value survey were used to collect the data. Data was analyzed using Structural EquationModeling (SEM) method trough AMOS Program. Result showed work value factors, transactional and transformational leadership type influence to team effectiveness with psychological contract as mediator variable. Psychological contract give a significant contribution to team effectiveness, therefore it could be predictor to team effectiveness.Key word: psychological contract, team effectiveness, transformational leadership transactional leadership,